Analytical analysis of 2D couple stress flow of blood base nanofluids with the influence of viscous dissipation over a stretching surface - Rehman, Ali; İnç, Mustafa; Tawfiq, Ferdous M.; Bilal, Muhammad (World Scientific Publ Co Pte Ltd, 2025)
This study examines the effects of viscous dissipation, thermal radiation, nanofluid over a stretched surface, and viscous dissipation on a two-dimensional couple stress blood base for the enhancement of heat transfer rate. Gold and multiwall carbon nanotubes are two forms of nanoparticles that are taken into consideration, with blood serving as the base fluid. The NLPDE controls the considering problem. The NLPDE was converted to NODEs using the mentioned similarity transformation. The analytical method known as HAM was used to analyze the transform NODE analytically. Graphs are used to illustrate the effects of many parameters, such as magnetic factors, nanoparticle volume friction, velocity power index, PN, thermal radiation factors, and EN, which are derived from TE and VE. The current research work highlights how important it is to include viscous dissipation in nanofluid dynamics. The results show complex interactions among stretching, thermal properties, and micro-scale effects. The results may have an impact on the development and enhancement of biomedical devices and treatments that use nanofluidic systems, especially those that deal with blood.
Keywords: Mathematica software; stretching surface; nanofluid; HAM; MHD